Ingrained interests and path-dependency: Employees' acceptance of new management systems in a Chinese state-owned enterprise. (17th October 2022) - Yang, Guang; Yang, Lixin
Abstract : This study is a sociological exploration of changes and interrelationships between production systems, management systems and employment relations through a case study of a Chinese state-owned enterprise (SOE) which has undergone substantial restructuring and reforms in an agriculture-dominated region that has witnessed rapid industrialisation. It draws on data collected through qualitative interviews, focus group discussions and workplace observation and participation. The findings suggest that while market, efficiency and performance have become the dominant discourse in China's SOEs, various organisational actors have reconstructed their identities, engaged in constant negotiations and continued formal and informal rules that supported their interests.